Mindful Eating in Gurbani: A Yogic Perspective (VED International Journal of Arts, Commerce and Technology (VIJACT), 2026)
In Indian philosophical traditions, diet (Āhāra) is very important because it affects your health, mental balance, and spiritual growth. The Sattvic diet (Sāttvika Āhāra) is an idea in yogic philosophy that means eating healthy, pure food that helps you think clearly and become more spiritually aware. Although the terms "Sattvic diet" come from mostly Yogic and Ayurvedic writings, the sacred text of Sikhism, Gurbani, also talks about mindful and disciplined eating in a similar way.In this study, the teachings about food and dietary practices in Sri Guru Granth Sahib are looked at and interpreted using the ideas of Yogic philosophy. It uses qualitative textual analysis to group relevant verses from Gurbani into themes like food as a divine gift, eating in moderation, the purity and simplicity of food, how diet affects mental states, and how to get food in an ethical way. Our research shows that Gurbani and Yogic traditions have a lot in common when it comes to ideas like mindful eating, moderation, and how food affects spiritual health. The study shows how traditional food advice can help with health and living a more whole life.Keywords: Sikh philosophy, Sattvic diet, Mitahara, Gurbani,  mindful eating, Yogic Diet.